2015
DOI: 10.1039/c4ra14304c
|View full text |Cite
|
Sign up to set email alerts
|

High yield of renewable hexanes by direct hydrolysis–hydrodeoxygenation of cellulose in an aqueous phase catalytic system

Abstract: In aqueous phosphoric acid, cellulose was efficiently converted into hexanes using a Ru/C catalyst combined with layered compounds or silica-alumina materials. In this process, the direct production of hexanes from cellulose can be improved by suppressing the formation of isosorbide, which makes it difficult to yield hexanes by further hydrodeoxygenation. As the co-catalyst, layered compounds showed a significant inhibition effect on the formation of isosorbide from sorbitol due to the steric restrictions of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 62 publications
(176 reference statements)
4
46
0
Order By: Relevance
“…20 In this system, isosorbide was the most robust intermediate, which corresponded to former studies. 11,17,26 Numerous research efforts suggested Ru/C catalyzed hydrogenation and acid-catalyzed hydrolysis and dehydration played important roles in the formation of alkanes. 11,27−31 But the addition of layered compounds was crucial because they could dramatically suppress the formation of isosorbide.…”
Section: ■ Introductionsupporting
confidence: 60%
See 4 more Smart Citations
“…20 In this system, isosorbide was the most robust intermediate, which corresponded to former studies. 11,17,26 Numerous research efforts suggested Ru/C catalyzed hydrogenation and acid-catalyzed hydrolysis and dehydration played important roles in the formation of alkanes. 11,27−31 But the addition of layered compounds was crucial because they could dramatically suppress the formation of isosorbide.…”
Section: ■ Introductionsupporting
confidence: 60%
“…Sels and co-workers investigated conversion of cellulose to gasoline alkanes (nhexane, methylcyclopentane and n-pentane) by using H 4 SiW 12 O 40 -modified Ru/C (htRu/C) and H 4 SiW 12 O 40 catalytic system in water/n-decane. 11 In contrast, they proposed gasoline alkanes were mainly yielded from a different route, which they called the HMF (5-hydroxymethylfurfural) route. In this route, HMF, produced from dehydration of cellulose derived glucose, was the main intermediate that was transformed into gasoline alkanes via consecutive hydrogenation/ hydrogenolysis.…”
Section: ■ Introductionmentioning
confidence: 96%
See 3 more Smart Citations